Gesammelte Schriften II - Campenhausen, Axel, Freiherr von (Jus ecclesiasticum, 2014)
The edition combines articles written by Axel von Campenhausen during the past 20 years concerning questions of church law and state law pertaining to the churches, its historical principles and current problems. These articles examine fundamental issues and contracts between the state and the church, theological faculties, the integration of Muslims, the Protestant episcopate, the law on foundations and endowments and church membership rights.